Temperature alters susceptibility of Picea abies seedlings to airborne pollutants: The case of CdO nanoparticles - Večeřová, Kristýna; Večeřa, Zbyněk; Mikuška, Pavel; Coufalík, Pavel; Oravec, Michal; Dočekal, Bohumil; Novotná, Kateřina; Veselá, Barbora; Pompeiano, Antonio; Urban, Otmar (Environmental pollution (Barking, Essex, 2019)
Although plants are often exposed to atmospheric nanoparticles (NPs), the mechanism of NP deposition and their effects on physiology and metabolism, and particularly in combination with other stressors, are not yet understood. Exploring interactions between stressors is particularly important for understanding plant responses in urban environments where elevated temperatures can be associated with air pollution. Accordingly, 3-year-old spruce seedlings were exposed for 2 weeks to aerial cadmium oxide (CdO) NPs of environmentally relevant size (8-62 nm) and concentration (2 × 105 cm-3). While half the seedlings were initially acclimated to high temperature (35 °C) and vapour pressure deficit (VPD; 2.81 kPa), the second half of the plants were left under non-stressed conditions (20 °C, 0.58 kPa). Atomic absorption spectrometry was used to determine Cd content in needles, while gas and liquid chromatography was used to determine changes in primary and secondary metabolites. Photosynthesis-related processes were explored with gas-exchange and chlorophyll fluorescence systems. Our work supports the hypothesis that atmospheric CdO NPs penetrate into leaves but high temperature and VPD reduce such penetration due to stomatal closure. The hypothesis that atmospheric CdO NPs influences physiological and metabolic processes in plants was also confirmed. This impact strengthens with increasing time of exposure. Finally, we found evidence that plants acclimated to stress conditions have different sensitivity to CdO NPs compared to plants not so acclimated. These findings have important consequences for understanding impacts of global warming on plants and indicates that although the effects of elevated temperatures can be deleterious, this may limit other forms of plant stress associated with air pollution.
Keywords: Acclimatization; oxidy; globální oteplování; vysoká teplota; teplota; listy rostlin; Oxides; Pinus; Nanoparticles; Hot Temperature; Global Warming; CdO nanoparticles; Photosynthesis; Cadmium Compounds; Primary/secondary metabolites; Plant Leaves; aklimatizace; Metabolomics; fotosyntéza; nanočástice; Abies; Picea; jedle; Norway spruce; Temperature; smrk; Air Pollutants; Environmental Pollutants; látky znečišťující životní prostředí; semenáček; látky znečišťující vzduch; Seedlings; sloučeniny kadmia; borovice